Depressed Heart Rate Variability is Associated with Abnormal EEG, MRI, and Death in Neonates with Hypoxic Ischemic Encephalopathy - Vergales, Brooke D.; Zanelli, Santina A.; Matsumoto, Julie A.; Goodkin, Howard P.; Lake, Douglas E.; Moorman, J. Randall; Fairchild, Karen D. (American Journal of Perinatology, 2014)
Objective Asphyxia can lead to autonomic nervous system dysfunction, including depressed heart rate variability (HRV). We tested the hypothesis that low HRV is associated with adverse short-term outcomes of abnormalities on electroencephalogram (EEG) and brain magnetic resonance imaging (MRI) and death in neonates with hypoxic ischemic encephalopathy (HIE).Study Design Neonates undergoing hypothermia therapy for HIE underwent monitoring of HRV. HRV in the first day after birth and after hypothermia and rewarming (days 4–7) were analyzed in relation to death and severity of abnormal findings on EEG and MRI.Results A total of 37 neonates had data available in the first 24 hour after birth and 67 had data days 2 to 7. Depressed HRV was significantly associated with adverse outcomes of death or moderate-to-severe abnormalities on EEG or MRI. In the first 24 hours, the odds ratio (OR) of one or more adverse outcomes for every 10-millisecond decrease in HRV was 3.19 (95% CI, 1.3–7.8; p = 0.01). HRV improved over time but low HRV remained significantly associated with adverse outcomes days 4 to 7 (OR, 2.72; CI, 1.32–5.61; p < 0.01).Conclusions Monitoring HRV, which is reflected in the heart rate characteristic index, may provide useful adjunct information on the severity of brain injury in infants with HIE.
Keywords: hypoxic ischemic encephalopathy; heart rate variability; neonate; asphyxia; electroencephalogram